2021
DOI: 10.1016/j.tranon.2021.101065
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a prognostic immune signature for lower grade glioma that can be recognized by MRI radiomics features to predict survival in LGG patients

Abstract: Highlights The IMriskScore can predict the prognosis and immunotherapy efficacy of LGG patients. Based on deep learning models, MRI radiomics can be used to predict the IMriskScore. Mutations in CIC improve the prognosis of patients in the high IMriskScore group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 71 publications
1
19
0
Order By: Relevance
“…Radiomics involves the exploitation of MRI data to extract high-dimensional quantitative imaging features, which can be used to support clinical decision-making [ 5 6 ]. Although previous radiomics studies in the field of neuro-oncology have mainly focused on gliomas [ 7 8 9 10 11 12 ], there has been an increase in the number of studies on brain metastases. Indeed, radiomics studies have demonstrated promising results in the discrimination of brain metastasis from other tumors [ 13 14 15 16 17 18 19 20 ], identification of primary tumor types in patients with brain metastases [ 21 22 23 24 ], prediction of specific genetic mutations [ 25 26 27 28 29 ], prediction of survival [ 30 31 ], differentiation between radiation necrosis and brain metastasis [ 32 33 34 35 ], and prediction of outcome after radiosurgery [ 36 37 38 39 40 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics involves the exploitation of MRI data to extract high-dimensional quantitative imaging features, which can be used to support clinical decision-making [ 5 6 ]. Although previous radiomics studies in the field of neuro-oncology have mainly focused on gliomas [ 7 8 9 10 11 12 ], there has been an increase in the number of studies on brain metastases. Indeed, radiomics studies have demonstrated promising results in the discrimination of brain metastasis from other tumors [ 13 14 15 16 17 18 19 20 ], identification of primary tumor types in patients with brain metastases [ 21 22 23 24 ], prediction of specific genetic mutations [ 25 26 27 28 29 ], prediction of survival [ 30 31 ], differentiation between radiation necrosis and brain metastasis [ 32 33 34 35 ], and prediction of outcome after radiosurgery [ 36 37 38 39 40 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Etv4 was identified in the present study as possibly one of the most important regulators of oligodendrocytes. Previous studies have found that mutations in CIC promote malignant progression of gliomas and that Etv4 is implicated in the transcriptional regulation of CIC [30,31]. Interestingly, fibroblasts were covered in all three main modules (M1, M2, and M3).…”
Section: Discussionmentioning
confidence: 89%
“…Radiomics derived from MRI have been proposed as a reliable tool for accurate diagnosis and risk assessment in several cancer types, e.g. in cervical [ 37 ], brain [ 38 ], and breast [ 39 ]. Similarly, a study has reported that radiomics analysis based on MRI was an effective tool for preoperative risk stratification in EC [ 40 ].…”
Section: Discussionmentioning
confidence: 99%